Different techniques of static/dynamic guided implant surgery: modalities and indications. (October 2014) - Vercruyssen, Marjolein; Fortin, Thomas; Widmann, Gerlig; Jacobs, Reinhilde; Quirynen, Marc
Abstract: For computer‐guided surgery a static surgical guide is used that transfers the virtual implant position from computerized tomographic data to the surgical site. These guides are produced by computer‐aided design/computer‐assisted manufacture technology, such as stereolithography, or manually in a dental laboratory (using mechanical positioning devices or drilling machines). With computer‐navigated surgery the position of the instruments in the surgical area is constantly displayed on a screen with a three‐dimensional image of the patient. In this way, the system allows real‐time transfer of the preoperative planning and visual feedback on the screen. A workflow of the different systems is presented in this review.